Externalizing Europe: the global effects of European data protection - Annegret Bendiek; Magnus Römer (Digital Policy, Regulation and Governance, 2019)
[Purpose:] This paper aims to explain how the EU projects its own data protection regime to third states and the US in particular. Digital services have become a central element in the transatlantic economy. A substantial part of that trade is associated with the transfer of data, most of it personal, requiring many of the new products and services emerging to adhere to data protection standards. Yet different conceptions of data protection exist across the Atlantic, with the EU putting a particular focus on protecting the fundamental right to privacy. [Design/methodology/approach:] Using the distinction between positive and negative forms of market integration as a starting point (Scharpf, 1997), this paper examines the question of how the EU is projecting its own data protection regime to third states. The so-called California effect (Vogel, 1997) and the utilization of trade agreements in the EU's foreign policy and external relations are well researched. With decreasing effectiveness and limited territorial reach of its enlargement policy, the EU found trade agreements to be particularly effective to set standards on a global level (Lavenex and Schimmelfennig, 2009). The existence of the single market makes the Union not only an important locus of regulation but also a strong economic actor with the global ambition of digital assertiveness. In the past, establishing standards for the EU's vast consumer market has proven effective in compelling non-European market participants to join. [Findings:] As the globe's largest consumer market, Europe aims to project its own data protection laws through the market place principle (lex loci solutionis), requiring any data processor to follow its laws whenever European customers' data are processed. This paper argues that European data protection law creates a “California Effect”, whereby the EU exerts pressure on extra-territorial markets by unilateral standard setting. [Originality/value:] With its GDPR, the EU may have defused the problem of European citizens' data being stored and evaluated according to the US law. However, it has also set a precedent of extra-territorial applicability of its legislation – despite having previously criticized the USA for such practices. By now, international companies increasingly store data of European customers in Europe to prevent conflicts with EU law. With this decision, the EU will apply its own law on others' sovereign territory. Conflicts created through the extra-territorial effects of national law may contradict the principle of due diligence obligations but are nevertheless not illegitimate. They may, however, have further unintended effects: Other major economies are likely to be less reluctant in the future about passing legal provisions with extra-territorial effect.
Keywords: 330; privacy; data protection; digital trade; fundamental rights; California effect